1997
DOI: 10.1073/pnas.94.15.8255
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance, gene expression, and lignin characterization in a mutant pine deficient in cinnamyl alcohol dehydrogenase

Abstract: We have discovered a mutant loblolly pine (Pinus taeda L.) in which expression of the gene encoding cinnamyl alcohol dehydrogenase (CAD; EC 1.1.1.195) is severely reduced. The products of CAD, cinnamyl alcohols, are the precursors of lignin, a major cell wall polymer of plant vascular tissues. Lignin composition in this mutant shows dramatic modifications, including increased incorporation of the substrate of CAD (coniferaldehyde), indicating that CAD may modulate lignin composition in pine. The recessive cad-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
121
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(130 citation statements)
references
References 32 publications
4
121
0
Order By: Relevance
“…The value of A 1510 of the bm1 mutant is con-siderably lower compared with the wild type and bm1 heterozygote and there is a statistically significant difference between genotypes (P = 0.0007). A high ratio of A 1665 : A 1510 and A 1595 : A 1510 is indicative of the incorporation of coniferaldehyde residues in the cell wall (Mackay et al, 1997;Stewart et al, 1997). Both ratios are higher in the bm1 mutant, confirming the results from Wiesner reactions (Figure 2).…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…The value of A 1510 of the bm1 mutant is con-siderably lower compared with the wild type and bm1 heterozygote and there is a statistically significant difference between genotypes (P = 0.0007). A high ratio of A 1665 : A 1510 and A 1595 : A 1510 is indicative of the incorporation of coniferaldehyde residues in the cell wall (Mackay et al, 1997;Stewart et al, 1997). Both ratios are higher in the bm1 mutant, confirming the results from Wiesner reactions (Figure 2).…”
Section: Resultssupporting
confidence: 80%
“…Based on the FT-IR analysis, specifically because of the higher ratios of A 1665 : A 1510 and A 1595 : A 1510 , it is apparent that the cell walls of the bm1 homozygote contain higher levels of coniferaldehyde than the wild type and bm1 heterozygote. This agrees with the histochemical data from the Wiesner reactions and with observations on loblolly pine (Pinus taeda L.) (Mackay et al, 1997) and tobacco (Stewart et al, 1997) in which the expression of the gene encoding CAD had been reduced. In both instances this resulted in increased incorporation of coniferaldehyde in the cell wall.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Previous studies have indicated impairing different steps in monolignol biosynthesis results in reddish brown to tan stem and stalk pigmentation, including the CAD and COMT mutants examined in this study (Mackay et al 1997, Tsai et al 1998, Sibout et al 2005, Zhang et al 2006). There are differences in pith and midrib (leaf vein) coloration between bmr6 and bmr12 (Porter et al 1978, Saballos et al 2009), probably because bmr6 and bmr12 block different steps of the monolignol biosynthetic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…At first sight, this makes it unlikely that lignin composition or concentration can be modified without detrimental effects to the plant. However, natural mutants carrying lesions in the biosynthetic pathway of lignin like the bm3 mutant of maize (mutation in the COMT gene, Vignols et al 1995), the fah1 mutant of Arabidopsis (mutation in the F5H gene, Meyer et al, 1996) and a CAD mutant of loblolly pine (MacKay et al 1997) show that changes in lignin composition and concentration are not lethal to the plant (Boudet 1998).…”
Section: Modifications In Lignin Content and Compositionmentioning
confidence: 99%